Patellar fractures are associated with an increased risk of total knee arthroplasty: A Matched Cohort Study of 6096 Patellar Fractures with a mean follow-up of 14.3 Years. (November 2018) - Larsen, P.; Rathleff, M. S.; Østgaard, S. E.; Johansen, M. B.; Elsøe, R.
Abstract : Aims: The aim of this study was to investigate the incidence of knee arthroplasty and arthroscopy following patellar fractures, and to compare this with an age- and gender-matched group without a prior patellar fracture. Patients and Methods: A national matched cohort study based on the Danish National Patient Register including all citizens of Denmark (approximately 5.3 million) was undertaken. A total of 6096 patients who sustained a patellar fracture in Denmark between 1 January 1996 and 31 December 2000 were included. The median age of these patients was 50.6 years (interquartile range (IQR) 28.5 to 68.9); 49.1% were women. Patients were followed-up until 31 December 2015, with regard to treatment with knee arthroplasty and/or knee arthroscopy. Results: Patients with a patellar fracture had an increased risk of knee arthroplasty (hazard ratio (HR) 1.83, 95% confidence interval (CI) 1.57 to 2.13) compared with citizens without a patellar fracture, and the effect was strongest during the first five years (HR 3.02, 95% CI 2.26 to 4.03). Patients with a patellar fracture also had a higher risk of knee arthroscopy (HR 3.94, 95% CI 3.49 to 4.46), and the effect was highest during the first five years after the fracture (HR 7.40, 95% CI 6.32 to 8.66). Conclusion: Patellar fractures are associated with an increased risk of knee arthroplasty and knee arthroscopy. The consequences of a patellar fracture may be more severe than previously considered, and patients must expect a lifelong increased risk of knee arthroplasty. Cite this article: Bone Joint J 2018;100-B:1477–81.